2018
DOI: 10.1680/jadcr.16.00151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of citric acid on the rheology, hydration and strength development of alkali aluminosilicate cement

Abstract: Alkali-activated aluminosilicate cements, as a sustainable and high-performance class of cementitious materials, can benefit from the development of admixtures that can enhance various aspects of their performance. Alkali activation generally occurs at a faster pace than the hydration of Portland cement (PC). In this investigation, citric acid was evaluated as an admixture for controlling the hydration kinetics, enhancing the fresh-mix rheology and delaying the setting of alkali aluminosilicate cement (AAC) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that several additives can be used to enhance the rheological characteristics of alkali activated binders. The addition of citric acid has altered the rheological characteristics of alkali activated binder; the use of 3 wt.% has produced alkali activated binder that has similar yield stress and viscosity that are comparable to those of Portland cement concrete [31].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that several additives can be used to enhance the rheological characteristics of alkali activated binders. The addition of citric acid has altered the rheological characteristics of alkali activated binder; the use of 3 wt.% has produced alkali activated binder that has similar yield stress and viscosity that are comparable to those of Portland cement concrete [31].…”
Section: Resultsmentioning
confidence: 99%
“…This will be discussed further in Section 2.4. Many chemical retarders for PC are not compatible with AAMs [60], but citric acid [61], d-gluconic acid [62], borate and phosphate [63] have all been described to give useful retardation in specific cases. However, the appropriate selection of a retarder depends critically on the role and content of calcium within the alkali-activation process; high-calcium mixes tend to be more effectively retarded by small organics that can complex Ca 2+ as it is released from the solid precursor and thus delay the precipitation of C-A-S-H type gels, whereas low-calcium mixes appear to be more amenable to the use of inorganic retarders.…”
Section: Chemical Admixturesmentioning
confidence: 99%
“…The effect of two types of retarders (citric acid and boric acid) on the reaction progress of mixture S38 defined with an H 2 O/Na 2 O ratio of 38 was studied. The admixture contents were established from patent recommendations and previous studies [10][11][12][13]. The retarder was added after the preparation of the activation solution and just before the incorporation of the slag.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings revealed that the addition of fly ash leads to a delay in the structuring process, while an increase in the water-to-solid ratio induced an acceleration at an early age. Various patents and studies have shown that admixtures can effectively delay the setting of activated slags [10][11][12][13]. A recent study showed the use of borax and citric acid was more effective than sucrose in extending the setting time of alkali-activated slags [14].…”
Section: Introductionmentioning
confidence: 99%